Comparison of Post Operative Pain Score between Doppler-Guided Hemorrhoidal Artery Ligation and Recto Anal Repair with Open Hemorrhoidectomy on Internal Hemorrhoid Grade III-IV at Siloam Hospitals Lippo Village - Sudirman, Taufik; Kosasih, Joanna Audricia (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Background: Hemorrhoids are a common lesion affecting 5% of the general population. Open hemorrhoidectomy has been considered a gold standard. However, this method has a significant score of postoperative pain Because of this side effect, another alternative method to treat hemorrhoids has been invented which can reduce post-operative pain. One of these methods is doppler-guided hemorrhoidal artery ligation and rectoanal repair (DGHAL-RAR). This study aims to know the comparison of the postoperative pain score between doppler-guided hemorrhoidal artery ligation and rectoanal repair compared with open hemorrhoidectomy.Method: The sample population of this study is internal hemorrhoid grade III-IV patients at Siloam Hospitals Lippo Village from 2018-2020. Visual analog scale data are taken from medical records. Sample data is obtained using a consecutive sampling method until 64 samples are met. The data obtained will be processed with the Mann U-Whitney test.Results: Incidence of postoperative pain more than VAS 3 occurred in DGHAL- RAR and open hemorrhoidectomy is 81,3% and 96,9% with a p-value of 0,104. The average score of Visual Analogue Scale score in DGHAL-RAR and open hemorrhoidectomy are 1,97 and 3,13 with a p-value of 0,001.Conclusion: This study shows that the comparison of pain scores in DGHAL-RAR and open hemorrhoidectomy is not statistically significant. The mean score of the Visual Analogue Scale Score in the DGHAL-RAR group is statistically significantly lower than the mean score in the open hemorrhoidectomy group.